Cuantificación de fenitoína sódica en cápsulas de acción inmediata que se dispensan en el distrito de trujillo” - Arteaga Honorio, Weimar Paúl (2008)
In this work we determined the content of sodium phenytoin in capsules of rapid action sold in the district of Trujillo, four formulations, two of them (Epamin and Felantin) are brand-name medicaments and the other two are generic medicaments (Lab. Corporation Infarmasa and Medifarma). The objective was to evaluate the accomplishment of the different analyzed batches, with the specification of potency established by the USP 31. The batches were obtained in different pharmaceutical establishments of Trujillo. We worked with the methodology described in the USP 31, using a HPLC Lachtrom Elite machine which has its column fulfilled of material L1 (250mm, 4mm, 5um), collated to a detector with fixing of diodes. Having as a result, the approval of all the batches